Pengaruh Brand Image Terhadap Customer Satisfaction Dengan Perceived Service Quality Dan Customer Engagement Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa Universitas Islam Malang Pengguna Aplikasi Grabbike) - Mohammad Iqbal Kusuma Adrian; Jeni Susyanti; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
This research was conducted to test the effect Brand Image to Customer Satisfaction with Perceived Service Quality and Customer Engagement as a case study Intervening Variable on Students of the Islamic University of Malang who use the application Grabbike. The population in this study was 3,869 students. The sampling technique used is Purposive Sampling and obtained 98 students. The data collection method used is the distribution of questionnaires and the method of analysis is descriptive statistical method, classical assumption test, partial least square, mediation test, with SmartPLS 3.0 tool. Research results show that brand image no significant effect on customer satisfaction. Brand image no significant effect on perceived service quality. Brand image significant effect on customer engagement. Perceived service quality significant effect on customer satisfaction. Customer engagement significant effect on customer satisfaction. Brand image no significant effect on customer satisfaction through perceived service quality. Brand image significant effect on customer satisfaction through customer engagement.  Keywords: brand image, perceived service quality, customer engagement, customer satisfaction